Response of Eragrostis plana and Eragrostis pilosa (L.) P. Beauv. submitted on flooded soil - Carloto, Bruno Wolffenbüttel; Escobar, Otávio dos Santos; Trivisiol, Vinicius Severo; Peripolli, Mariane; Pivetta, Maicon; Posser, Taiana; Barreto, Eduarda Preto Mena; Dornelles, Sylvio Henrique Bidel (Acta Scientiarum. Biological Sciences, 2020)
The development of Eragrostis plana and Eragrostis pilosa was evaluated in a greenhouse when submitted to different soil moisture conditions. The design was completely randomized, consisting of a factorial 2x3, with the following factors: Eragrostis accessions and soil moisture levels (50% of water retention capacity (WRC), 100% of WRC and soil with water depth of 10 cm). The morphological-anatomical parameters of the plants were evaluated and the aerenchyma and adventitious roots were quantified. In addition, the photosynthetic pigments and the electron transport capacity of the photosynthetic chain were quantified, with the intention of verifying if the amount of water in the soil interferes with these parameters. Similar responses were observed between the two species when submitted to a water table environment, where there were larger aerenchymal formations in the roots and stems, as well as adventitious roots at the soil surface, inferring adaptations for survival to anaerobic stress. Negative effects on the transport of electrons and the formation of chlorophyll pigments were observed for both species when submitted to the hypoxic environment and, consequently, there was reduction of dry mass of shoot and roots, as well as reduction in the emission of tiller. It is concluded that the irrigation water management and the water blade in the rice crop are important, together with the control of invasive plants, considering the negative effects caused to the growth and development of these plants